Didactical Design with Motion Graphics for Enhancing Conceptual Understanding of Geometric Translation - Rosita, Cita Dwi; Noto, Muchamad Subali; Anggraini, Lilis Marina; Rahadi, Ikman Nurhakim (Department of Mathematics Education Program IPI Garut, 2025)
Pembelajaran transformasi di sekolah menengah menghadapi rendahnya pemahaman konseptual siswa. Desain didaktis berbasis visual dinamis belum terintegrasi sistematis dengan analisis hambatan belajar. Penelitian ini bertujuan menganalisis penguatan pemahaman konseptual translasi melalui desain didaktis berbantuan motion graphic. Penelitian ini menggunakan pendekatan kualitatif dengan tiga fase DDR, yaitu analisis didaktis dan pedagogis, analisis metapedadidaktik, serta analisis retrospektif. Subjek penelitian terdiri dari 10 siswa yang dipilih secara purposif untuk memungkinkan pengamatan mendalam terhadap proses belajar, respons didaktis, dan regulasi hambatan belajar. Data dikumpulkan melalui observasi, wawancara, dan tugas tertulis. Hasil menunjukkan seluruh siswa memahami translasi sebagai pergeseran. Sebanyak 30% siswa mengalami hambatan epistemologis pada interpretasi vektor translasi negatif. Umpan balik visual motion graphic memungkinkan koreksi mandiri selama pembelajaran. Hambatan belajar bergeser dari epistemologis menuju didaktis pada aspek komunikasi matematis formal. Desain didaktis berbantuan motion graphic efektif meregulasi hambatan belajar translasi. Penelitian lanjutan perlu memperluas pada transformasi geometri lain. Learning transformations in secondary schools faces persistently low students’ conceptual understanding. Didactical designs based on dynamic visualization have not been systematically integrated with learning obstacle analysis. This study aims to analyze the strengthening of students’ conceptual understanding of translation through motion graphic–assisted didactical design. This study employed a qualitative approach with three phases of Didactical Design Research (DDR), namely didactical and pedagogical analysis, metapedadidactical analysis, and retrospective analysis. The participants consisted of ten purposively selected students to allow in-depth observation of learning processes, didactical responses, and the regulation of learning obstacles. Data were collected through observations, interviews, and written tasks. Retrospective analysis compared actual student responses with predicted didactical responses. Source triangulation ensured the credibility of research findings. Results show that all students understood translation as a rigid displacement. Thirty percent experienced epistemological obstacles in interpreting negative translation vectors. Visual feedback provided by motion graphics enabled self-correction during learning. Learning obstacles shifted from epistemological to didactical, particularly in formal mathematical communication. Motion graphic–assisted didactical design effectively regulates learning obstacles in translation. Future studies should extend to other geometric transformations.